Effectiveness of different surgical methods in treatment of thrombosis of arteriovenous fistula in hemodialysis patients - LIU Ming-sheng; ZHOU Hong-qing; DENG Ti-bin (Linchuang shenzangbing zazhi)
Objective To investigate the surgical effect of two methods: proximal reconstruction dynamic venous fistula angioplasty and anastomotic orthotopic thrombectomy re-angioplasty in treating patients with thrombosis of arteriovenous fistula in hemodialysis patients. Methods We selected 102 patients with venous fistulas thrombosis in our hospital from September 2009 to July 2014. There were 64 males,with an average age of( 44. 3 ± 2. 7) years,and 38 females,with an average age of( 45. 2 ± 1. 9) years. In 102 patients,60 cases were treated with proximal reconstruction of arteriovenous fistula,of which 38 were male and22 were female,with an average age of( 46. 1 ± 2. 4) years old. The average time of internal fistula was( 16. 3 ± 3. 1) months,and the average time of thrombosis was( 72. 5 ± 0. 4) h. Forty-two cases were treated by thrombectomy in situ anastomosis re-angioplasty. There were 26 males and 16 females. The average age was( 47. 5 ± 3. 2) years old,the average time of fistula was( 16. 9 ± 2. 9) months,and average thrombosis time was( 72. 1 ± 0. 3) h. The success rate,anastomotic incidence of stenosis within 1 year after operation and recurrent rate of thrombosis were compared between two surgical operations. Results Of 60 cases subject to proximal reconstruction of arteriovenous fistula,the surgical success rate was 95. 0%,anastomotic stenosis occurred in 5 cases( 8. 8%) after 1 year,and thrombosis recurred in 4 cases( 7%). Twenty cases were successfully treated with embolectomy at the anastomotic site with a success rate of 61. 9%. Anastomotic stricture occurred in 9 cases( 35. 4%) after 1 year,and thrombosis reoccurred in 5 cases( 19. 2%)( P< 0. 01). Conclusions In comparison to in situ thrombectomy re-angioplasty,the proximal reconstruction of arteriovenous fistula angioplasty in the treatment of thrombosis of iliac artery fistula in hemodialysis patients can obviously reduce the incidence of stenosis and thrombosis of the postoperative anastomotic stoma,and the curative effect is significant.